Seborrheic keratosis at the cavum concha of the pinna: a case report - Sahoo, Soumick R.; Nilanjan Datta; Nayak, Pallavi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Seborrheic keratosis is a benign cutaneous tumour. The most common sites include head, neck, trunk and extremities except palms and soles. Pinna is a very rare site for such a lesion. They mostly present as multiple small lesions and solitary large lesion is very rare. Ultraviolet light exposure and human papilloma virus infection are possible etiologies. The differential diagnosis may include various benign lesions along with malignancy. The treatment options include removal of the tumour by simple surgical excision or by other means such as laser ablation. The confirmation of the diagnosis is by histopathological examination of excised specimen. There may be chances of recurrence of the lesion and so close follow up is required. We are reporting a brownish lesion at the cavum concha of left ear pinna appreciated since 1 year following thermal injury sustained during the welding work. The lesion was surgically excised and histopathology confirmed it as seborrheic keratosis. Patient has been followed up for 6 months and no recurrence noted.